Acquired resistance to immunotherapy in MMR-D pancreatic cancer. Issue 1 (20th November 2018) - Hu, Zishuo Ian; Hellmann, Matthew D.; Wolchok, Jedd D.; Vyas, Monika; Shia, Jinru; Stadler, Zsofia K.; Diaz, Luis A.; O'Reilly, Eileen M.
Abstract : Background: MMR-D pancreatic cancer have been reported to respond to checkpoint inhibitor therapy. Here, we report the first case of acquired resistance to immunotherapy in MMR-D pancreatic cancer. Case presentation: A 45-year-old woman with unresectable MMR-D pancreatic cancer was initially treated with FOLFIRINOX, FOLFIRI, and stereotactic body radiation with stable disease burden. After 3 months, imaging showed progression of disease with an increase in CA19-9. She was subsequently enrolled in a clinical trial of an anti-PD-L1 antibody in combination with an IDO1 inhibitor. She demonstrated a partial response to therapy by RECIST 1.1 criteria with declining tumor markers. Twenty-two months after beginning immunotherapy, imaging revealed an increasing left ovarian cystic mass. There were no other sites of progressive disease. The patient underwent a total hysterectomy and bilateral salpingo-oophorectomy, appendectomy, omentectomy and pelvic lymphadenopathy. Pathology was consistent with a metastasis from the pancreas involving the endometrium and left ovary. Thereafter, the patient continued with PD-1 blockade therapy off protocol with no further progressive disease. Immune profiling showed high levels of CD8+ T cells and PD-1 positive immune cells infiltrating the tumor, with a moderate level of PD-L1 expression in both the immune cells and the tumor cells. Next generation sequencing found only the KRAS G12D and RNF43 G659Vfs*41 mutations were retained from the pre-treatment tumor in the treatment-resistant tumor. Conclusions: This is the first report describing acquired resistance to immunotherapy in MMR-D pancreatic cancer with accompanying genomic and immune profiling. This case of oligoprogression in the setting of immunotherapy demonstrates the feasibility of localized treatment followed by continuation of immunotherapy to sustain ongoing response.